Bladder hematoma as an unusual cause or consequence of obstructed labour - Para, Shikha; Jain, Shaveta; Sirohiwal, Daya; Nanda, Smiti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Bladder hematoma is a rare complication but also an unusual mechanical cause of obstructed labour, whose incidence in India is 1-2%. The most common reason for intraluminal urinary bladder hematoma is trauma, but it can occur with cystitis, pelvic malignancy and irradiation. A large hematoma may mimic a neoplastic mass on imaging. We reported a first case of bladder hematoma as a cause or result of obstructed labour in a multipara where the diagnosis was made intraoperatively. This bladder complication also became the indication for classical caesarean section, the technique which is almost obsolete nowadays, where the indication for classical caesarean section was obligatory.